Antioxidant properties of the methanolic extract of avocado fruit peel (Persea americana Mill.) from Indonesia - Nurdin Rahman; Sri Mulyani Sabang; Rukman Abdullah; Bohari Bohari (Wolters Kluwer Medknow Publications, 2022)
This study analyzed the antioxidant activity and the phytochemical substances in avocado fruit peel extracted with methanol. In this study, antioxidant activity was determined by IC50 based on the regression value of DPPH free radicals' inhibition. Phytochemical content was measured qualitatively concerning the total content of phenols, flavonoids, tannins, saponins, and alkaloids. Our measurements showed that the methanolic extract of avocado fruit peels from Indonesia had the value of each phytochemical compound as follows: total phenol was 21.833 ± 0.118 mg/100 g extract; total flavonoids were 2.607 ± 0.111 mg/100 g extract; total tannin was 38.357 ± 0.202; saponin content was 8.874% ± 0.031%; and total alkaloid was 9.95 ± 0.035 mg CE/g extract. They then provided the antioxidant activity in IC50, which reached 185.891 ± 1.598 ppm. Avocado fruit peels are identified as a phytochemical source that contributes to antioxidant activities.